Hadith #5377 - Sahih al-Bukhari - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي (Sahih al-Bukhari)
that he heard the Prophet (ﷺ) saying, “From among my followers there will be some people who will consider illegal sexual intercourse, the wearing of silk, the drinking of alcoholic drinks and the use of musical instruments, as lawful. And there will be some people who will stay near the side of a mountain and in the evening their shepherd will come to them with their sheep and ask them for something, but they will say to him, ‘Return to us tomorrow.’ Allah will destroy them during the n
Grade: Sahih